Safety and tolerability of SARS‐Cov‐2 vaccination in patients with myasthenia gravis: A multicenter experience. (17th April 2022) - Farina, Antonio; Falso, Silvia; Cornacchini, Sara; Spagni, Gregorio; Monte, Gabriele; Mariottini, Alice; Massacesi, Luca; Barilaro, Alessandro; Evoli, Amelia; Damato, Valentina
Abstract: Background and purpose: During the COVID‐19 pandemic, myasthenia gravis (MG) patients have been identified as subjects at high risk of developing severe COVID‐19, and thus were offered vaccination with priority. The lack of direct data on the safety and tolerability of SARS‐CoV‐2 vaccines in MG have contributed to vaccine hesitancy. To address this issue, the safety and tolerability of SARS‐CoV‐2 vaccines were assessed in a large cohort of MG patients from two referral centers. Methods: Patients with confirmed MG diagnosis, consecutively seen between October and December 2021 at two MG centers, were enrolled. Demographics, clinical characteristics, and information regarding SARS‐CoV‐2 infection/vaccination were extracted from medical reports and/or collected throughout telephonic or in‐person interviews. Results: Ninety‐eight (94.2%) of 104 patients included were administered at least two vaccine doses 4 weeks before the interview or earlier, and among them, 63 of 98 (64.2%) have already received the "booster" dose. The most frequently used vaccines were BNT162b2‐Pfizer‐BioNTech and mRNA‐1273‐Moderna. Overall, only minor side effects were reported, most commonly local pain and fever. MG worsening after vaccination was observed in eight of 104 (7.7%) cases. The frequency of worsening among muscle‐specific tyrosine kinase MG cases (3/9, 33.3%) was significantly higher compared to other serological subgroups. Spontaneous symptom regression was observed in six of eight cases. Twelve of 104 (11.5%) patients had SARS‐CoV‐2 infection, and none of the SARS‐CoV‐2‐infected MG patients worsened after vaccination. Conclusions: Our data support the safety and tolerability of mRNA COVID‐19 vaccines, which should be strongly recommended in MG patients, who could be at higher risk of complications if exposed to SARS‐CoV‐2 infection. Abstract : The lack of direct data on the safety and tolerability of SARS‐CoV‐2 vaccines in myasthenia gravis (MG) have contributed to vaccine hesitancy. In this large, multicenter study, we showed that only minor side effects were reported and disease exacerbation after COVID‐19 mRNA vaccines exposure was rare, with spontaneous resolution of symptoms in most cases. Overall, these findings support the safety of COVID‐19 mRNA vaccines in MG.